Land Degradation and Landslide in Indonesia - Sitorus, Santun R.P.; Pravitasari, Andrea Emma (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Land degradation is one of the causes of lack of success of agricultural activities in Indonesia because of a decline in land productivity continuously and ultimately reduce the level of income / welfare of farmers. Land degradation can occur either on dry land or in wetlands, so prevention and / or rehabilitation of degraded land is very important that the agricultural area can be used on an ongoing basis. Land degradation is the loss or reduction of utility or potential use of land, loss of or changes in land features that are not hindered replaced. According to FAO (1993), soil degradation is a process that describes the phenomenon which lower the capacity of soil to support life. Land degradation is a process of decline of soil productivity, temporary or permanent, so that eventually the land can lead to a certain critical level (Dent, 1993). The process includes various forms of land degradation levels.